Impact of Combined Antiretroviral Treatment (cART) on Latent Cytomegalovirus Infection - Aura Temereanca; Luminita Ene; Gratiela Tardei; Camelia Grancea; Cristian L. Achim; Simona Ruta (Viruses)
Cytomegalovirus infections and reactivations are more frequent in people living with HIV (PLWH) and have been associated with increased risk of HIV progression and immunosenescence. We explored the impact of combination antiretroviral therapy (cART) on latent CMV infection in 225 young adults parenterally infected with HIV during childhood. Anti-CMV IgG antibodies were present in 93.7% of participants, with lower levels correlating with longer cART exposure and better immunologic parameters. Patients with immunological treatment success (CD4 > 350 cells/mL) had significantly lower CMV IgG titers compared to those with suboptimal immune response to cART. In total, 78% of the tested patients had robust CMV-specific T-cell responses, measured by an IFN-γ release assay. A good immune response to treatment was significantly associated with CMV-specific cellular immunity: IFN-γ level was positively correlated with CD4 and CD8-T cell counts. No differences were observed between patients with suppressed/non-suppressed HIV viremia in terms of CMV humoral and cellular immune response. CMV DNA was detected in only 17% of participants, with lower levels among those with cART-induced immune recovery. The successful antiretroviral treatment with subsequent immunologic reconstitution may lead to restoration of CMV-specific immune responses and effective control of latent infection, limiting episodes of CMV reactivation in HIV-positive individuals.